The Influence of Organizational Climate and Motivation on Organizational Commitment of Generation Z in Jemaat GMIT Pniel Batuinan - Klasis Semau - Wadu, Yulius D. Mau; Lero, Yulita Y.; Winarto, Jacinta (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to examine the influence of organizational climate and motivation on organizational commitment among Generation Z members of the GMIT Pniel Batuinan Congregation. Using a quantitative approach, data were collected through questionnaires completed by 39 respondents selected through a saturated sampling technique from the population of Generation Z congregants. The independent variables consist of organizational climate and motivation, while the dependent variable is the level of organizational commitment. Data analysis using multiple linear regression showed that organizational climate had a positive effect, while motivation had no effect on member commitment. The coefficient of determination of 0.768 indicates that approximately 76.8% of the variation in organizational commitment can be explained by these two variables. The results of this study emphasize the importance of implementing a conducive organizational climate and providing appropriate motivation to increase the commitment of Generation Z in the church environment, thereby supporting the sustainability of cadre development programs and congregation growth.